THE GROWTH OF CHLORELLA VULGARIS CULTURED IN LIQUID ORGANIC FERTILIZER OF WATER HYACINT H (EICHHORNIA CRASSIPES) AT DIFFERENT SALINITIES - Iba, Wa; Utami, Citra; Balubi, M. (Indonesian Aquaculture Society (MAI), 2019)
This study aims to determine the effect of salinity on the growth of microalgae C. vulgaris cultured in 5% concentration of water hyacinth liquid organic fertilizer. The research used a completely randomized design with four salinity treatments at 30, 35, 40 and 45 ppt in triplicates. The volume of culture media was 150 mL that consisted of 142.5 ml of sterile sea water and 7.5 ml of water hyacinth organic fertilizer. The increase in microalgae cell density was observed every other day using haemocytometer under light microscope. The culture was harvested after they reached stationary phase at day 8. Culture age (p= 0,00<0.05) and salinity (p= 0,00<0.05) affected the growth, dry weight and biomass productivity of C. vulgaris. Cells density and yield in all salinities tested was significantly different (p= 0,00<0.05) at stationary phase of growth. Higher cell density, specific growth rate, yield, dry weight and biomass productivity were observed in 40 ppt salinity compared to other salinities. At 40 ppt, cell density was 85.33 x 104 cells. ml-1 as well as specific growth rate that was at 0.839 cells.day-1, with the highest average yield of C. vulgaris was observed on day 6 and day 8 (exponential to stationary phase) at 115, 3 x 104 cells.ml-1. Similarly, considerably higher dry weight at 40 ppt was observed at 0.038 g.L-1 with biomass productivity at 0.032 g.L-1.day-1 compared to other salinities tested However these results were not significantly different (p=0.7>0.05) from other salinities. This study suggested that 40 ppt can be used to culture C. vulgaris in 5 % concentration of water hyacinth organic medium to obtain better growth and higher biomass production.